2015
DOI: 10.1002/jor.22965
|View full text |Cite
|
Sign up to set email alerts
|

Localization of bone morphogenetic protein 13 in human intervertebral disc and its molecular and functional effects in vitro in 3D culture

Abstract: Our laboratory has demonstrated that bone morphogenetic protein 13 prevented the effects of annular injury in an ovine model, maintaining intervertebral disc height, cell numbers and increasing extracellular matrix production compared to degenerated controls. The present study sought to examine the molecular effects of bone morphogenetic protein 13 on human degenerated disc cells and localize its expression in both human degenerate and scoliotic disc tissue. Effect of bone morphogenetic protein 13 on human der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 32 publications
4
17
0
Order By: Relevance
“…These data are reinforced by other investigations in our laboratory, which have demonstrated similar patterns of GAG production in human IVD cells when cultured with CDMP-2. 32 This, conversely, validates our study, as the results derived from the cell line appear to resemble the effect CDMP-2 has on endogenous disc cells. Our results are further supported by previous reports of enhanced proteoglycan production in response to in vivo CDMP-2 injection into injured ovine IVD.…”
Section: Discussionsupporting
confidence: 87%
“…These data are reinforced by other investigations in our laboratory, which have demonstrated similar patterns of GAG production in human IVD cells when cultured with CDMP-2. 32 This, conversely, validates our study, as the results derived from the cell line appear to resemble the effect CDMP-2 has on endogenous disc cells. Our results are further supported by previous reports of enhanced proteoglycan production in response to in vivo CDMP-2 injection into injured ovine IVD.…”
Section: Discussionsupporting
confidence: 87%
“…Through adenoviral‐mediated overexpression studies, Zhang et al compared the effects overexpressing various BMP family molecules on ECM accumulation in bovine AF cells and demonstrated GDF6 overexpression induced one of the most significant PG and collagen production responses . In 3D alginate bead cultures of human NP and AF cells, GDF6 supplementation increased both PG and collagen production . Interestingly, at high concentrations (800 ng/mL) GDF6 was also shown to act as a potent chemoattractant for NP cells with similar responses observed to potent chemoattractants, such as fetal calf serum (FCS) .…”
Section: The Effect Of Supplementation With Gdfs On Disc Cells and Chmentioning
confidence: 99%
“…This potential interaction of GDFs and proinflammatory molecules hints at the presence of a natural equilibrium that is dysregulated during degeneration, though this relationship appears to be complex. In vitro, GDF6 increases ECM production in degenerate NP cells, while in vivo GDF6 treatment prevented ECM degradation in a sheep model . GDF5 has been shown to directly inhibit the expression of MMP‐13 and ADAMTS4 in human chondrocytes and expression of other proinflammatory markers such as TNF‐α, IL‐1β, and prostaglandinE2 (PGE2) in murine NP cells .…”
Section: Gdfs In Ivd Development Homeostasis and Potential For Regenmentioning
confidence: 99%
“…One growth factor recently proposed for NP regeneration is growth differentiation factor 6 (GDF6), a member of the bone morphogenetic protein (BMP) family that plays important developmental roles in the formation of cartilaginous tissues, including the IVD (Clendenning & Mortlock, 2012;Settle et al, 2003;Tassabehji et al, 2008;Wei et al, 2016). GDF6 expression has been linked to anti-ageing effects in multiple tissues (Hisamatsu, Ohno-Oishi, Nakamura, Mabuchi, & Naka-Kaneda, 2016) and, whereas studies conducted in our laboratory and others do not suggest GDF6 expression decreases with degeneration (Gulati, Chung, Wei, & Diwan, 2015; Le Maitre, Freemont, & Hoyland, 2009), preclinical studies have demonstrated that injection of GDF6 into experimentally induced rabbit and ovine annular puncture models attenuates pro-inflammatory molecular changes and prevents progression of IVD degeneration (Miyazaki et al, 2018;Shen et al, 2009). However, the hypocellular nature of the tissue and the aberrant phenotype of degenerate NP cells suggests that growth factor therapy alone may be insufficient to promote regeneration of human IVD.…”
Section: Introductionmentioning
confidence: 95%